The Role of Bay Leaf Extract in Reducing Liver Inflammation in Mice (Mus Musculus) Induced by Potassium Oxonate - Silvia Awwalia, Evy; Masdan Salim, Hotimah; Faishal Riza, Mochammad; Mulyadi, Mulyadi (Jurnal Ilmiah Kesehatan, 2024)
Hyperuricemia is characterized by elevated uric acid levels in the blood, often stemming from increased uric acid production or inadequate uric acid excretion, resulting in levels exceeding 7 mg/dL. If left unmanaged, this condition can lead to gout arthritis. Elevated serum uric acid levels have also been linked to liver damage, as evidenced by findings in patients diagnosed with Non-alcoholic fatty liver disease (NAFLD), showing increased serum uric acid levels associated with liver damage. This study investigates the potential role of bay leaf extract in reducing liver inflammation related to uric acid metabolism. This study employed a true experimental approach with a post-test control group design, utilizing 8-week-old Mus musculus as experimental animals. The groups were divided as follows: Group 1 (control), Group 2 (Potassium oxonate-PO), Group 3 (PO with administration of bay leaf extract at 75mg/kg body weight), Group 4 (PO with administration of bay leaf extract at 150mg/kg body weight), and Group 5 (PO with administration of bay leaf extract at 300mg/kg body weight). Histological examination of the liver in the PO administration group revealed cell infiltration compared to the control group. However, a significant reduction in damaged hepatocyte cells was observed by administering bay leaf extract in PO+EDS-1, PO+EDS-2, and PO+EDS-3 groups (P<0.05). Bay leaf extract demonstrates hepatoprotective effects in hyperuricemia induced by potassium oxonate.